The influence of financial technology and capital adequacy ratio (CAR) on the financial performance of bank - Patricia, Vanessa; Daud, Ilzar; Malini, Helma; Wendy; Syahputri, Anggraini (Institute of Computer Science (IOCS), 2023)
The primary objective of the inquiry is to examine the impact of capital adequacy ratios and financial technology on banks' financial performance. This study utilised Capital Adequacy Ratio and Financial Technology as measured by Mobile Banking as independent variables. In this study, Financial Performance as determined by Return On Assets is the dependent variable, and the mediator variable is bank operational efficiency. The methodology used is a quantitative approach employing multiple regression analysis techniques. This analysis uses data from PT Mandiri Bank from 2018 to 2022. This investigation utilises secondary data as its source of information. Secondary data was extracted from Mandiri Bank's annual financial statements. The impact of mobile banking and capital adequacy ratio on return on assets is negligible and positive, respectively. Meanwhile, the ratio of Operational Costs to Operational Income has no impact on Mobile Banking's effect on ROA. There is no discernible effect of adjusting variable operational costs against operational income on the correlation between the capital adequacy ratio and return on assets